2019
DOI: 10.1007/s00259-019-04286-8
|View full text |Cite
|
Sign up to set email alerts
|

Baseline PET features to predict prognosis in primary mediastinal B cell lymphoma: a comparative analysis of different methods for measuring baseline metabolic tumour volume

Abstract: Purpose This study assessed the performance of four different methods for the estimation of metabolic tumour volume (MTV) in primary mediastinal B cell lymphoma (PMBCL). Method MTV was estimated using either a region growing automatic software program (RG) or a fixed threshold (FT) segmentation algorithm with the three most common cutoffs proposed in the literature (i.e., 25% and 41% of the SUVmax and SUV value ≥2.5). We compared these four methods using phantoms that simulated different setups of the main ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
1
14
1
1
Order By: Relevance
“…47 In this study, we use a segmentation method with a fixed-threshold at SUV ¼ 2.5 that has analogous accuracy and offers a better tumor coverage in comparison with the widely used percentage threshold at 41% of SUV max . 45,47,53 The median MTV in our cohort appears lower than in other series using the same fixed-threshold methodology 47 which may be easily explained by a relatively larger number of patient with early stage in our study.…”
Section: F I G U R Econtrasting
confidence: 56%
“…47 In this study, we use a segmentation method with a fixed-threshold at SUV ¼ 2.5 that has analogous accuracy and offers a better tumor coverage in comparison with the widely used percentage threshold at 41% of SUV max . 45,47,53 The median MTV in our cohort appears lower than in other series using the same fixed-threshold methodology 47 which may be easily explained by a relatively larger number of patient with early stage in our study.…”
Section: F I G U R Econtrasting
confidence: 56%
“…Different procedures and a wide range of threshold levels have been proposed to calculate MTV. 35,43,49 Moreover, the prognostic effect of MTV has been estimated using cut-points that are heavily cohort-dependent, being generated by ROC analysis of small series. In this study, we chose to use a segmentation method with a fixed-threshold at SUV 5 2.5 43 that, compared with the widely used percentage threshold at 41% of SUVmax, maintains a similar accuracy and offers better tumor coverage, 41 particularly in lesions with heterogeneous FDG uptake distribution.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we chose to use a segmentation method with a fixed-threshold at SUV 5 2.5 43 that, compared with the widely used percentage threshold at 41% of SUVmax, maintains a similar accuracy and offers better tumor coverage, 41 particularly in lesions with heterogeneous FDG uptake distribution. 49 Although the lack of standardization endangers the reproducibility of the results obtained in retrospective studies, there is increasing evidence of the prognostic value of quantitative parameters obtained from 18FDG-PET/CT in patients with different non-Hodgkin lymphoma subtypes. 17,26,28,50,51 We sought to use the quantitative parameters from PET scans to discriminate patient with different outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report looking at the differences that arise from tumour volume segmentation has shown that low MTV had a significantly longer progression-free survival and overall survival compared to patients with high MTV. These findings were obtained regardless of the segmentation methods used [29].…”
Section: Bin Sizementioning
confidence: 71%